( x - 2 )( x - 1 ) + 4( 3x + 2 )( x + 3 ) = 38
giúp mình với ạ!
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a: =>4/3x=7/9-4/9=1/3
=>x=1/4
b: =>5/2-x=9/14:(-4/7)=-9/8
=>x=5/2+9/8=29/8
c: =>3x+3/4=8/3
=>3x=23/12
hay x=23/36
d: =>-5/6-x=7/12-4/12=3/12=1/4
=>x=-5/6-1/4=-10/12-3/12=-13/12
Đề trước đó:
(x-7)(x+1)-(x-3)^2=(3x-5)(3x+5)-(3x+1)^2+(x-2)^2-x
<=>x^2+x-7x-7-x^2+6x-9=9x^2-25-9x^2-6x-1+x^2-4x+4-x
<=>x^2-11x-6=0
<=>x^2-2x. 11/2 + 121/4-145/4=0
<=>(x-11/2)^2=145/4
<=>|x-11/2|=căn(145)/2
<=>x=[11+-căn(145)]/2
S = 1x2 + 2x3 + 3x4 + ... + 38x39 + 39x40
3S = 1x2x3 + 2x3x3 + 3x4x3 + ... + 38x39x3 + 39x40x3
3S = 1x2x3 + 2x3x(4-1) + 3x4x(5-2) + ... + 38x39x(40-37) + 39x40x(41-38)
3S = 1x2x3 + 2x3x4-1x2x3 + 3x4x5-2x3x4 + ... + 38x39x40-37x38x39 + 39x40x41-38x39x40
S = 39x40x41 : 3
S = 21320
\(3S=1.2.3+2.3.3+...+39.40.3\)
\(3S=1.2.\left(3-0\right)+2.3.\left(4-1\right)+...+39.40.\left(41-38\right)\)
\(3S=0.1.2-1.2.3+1.2.3-2.3.4+...+38.39.40-39.40.41\)
\(3S=30.40.41\)
\(S=10.40.41\)
\(\left(\dfrac{2x}{3}-\dfrac{1}{3}\right)+\left(3x-2x+1\right)=8\)
\(\Leftrightarrow\dfrac{2x-1}{3}+x-7=0\Rightarrow2x-1+3x-21=0\Leftrightarrow x=\dfrac{22}{5}\)
\(\left(\dfrac{2}{3}x-\dfrac{1}{3}\right)+\left[3x-2\left(x-1\right)\right]=8\)
\(\Rightarrow\dfrac{2}{3}x-\dfrac{1}{3}+3x-2x+2=8\)
\(\Rightarrow\dfrac{5}{3}x=\dfrac{19}{3}\Rightarrow x=\dfrac{19}{5}\)
`@` `\text {Ans}`
`\downarrow`
`(8x-3)(3x+2)-(4x+7)(x+4)=(2x+1)(5x-1)-33`
`\Leftrightarrow 8x(3x+2) -3(3x+2) - 4x(x+4) + 7(x+4) = 2x(5x-1) + 5x-1 - 33`
`\Leftrightarrow 24x^2 + 16x - 9x - 6 - 4x^2 - 16x - 7x - 28 = 10x^2 - 2x + 5x - 1 - 33`
`\Leftrightarrow 20x^2 -16x - 34 = 10x^2 + 3x - 34`
`\Leftrightarrow 20x^2 - 16x - 34 - 10x^2 - 3x + 34 = 0`
`\Leftrightarrow 10x^2 - 19x = 0`
`\Leftrightarrow x(10x - 19)=0`
`\Leftrightarrow `\(\left[{}\begin{matrix}x=0\\10x-19=0\end{matrix}\right.\)
`\Leftrightarrow `\(\left[{}\begin{matrix}x=0\\10x=19\end{matrix}\right.\)
`\Leftrightarrow `\(\left[{}\begin{matrix}x=0\\x=\dfrac{19}{10}\end{matrix}\right.\)
Vậy, `x={0; 19/10}.`
\(1,\dfrac{3x+2}{6}-\dfrac{3x-2}{4}=\dfrac{15}{8}\\ \Leftrightarrow\dfrac{4\left(3x+2\right)}{24}-\dfrac{6\left(3x-2\right)}{24}-\dfrac{45}{24}=0\\ \Leftrightarrow12x+24-18x+12-45=0\\ \Leftrightarrow-6x-9=0\\ \Leftrightarrow x=-\dfrac{3}{2}\)
2, ĐKXĐ:\(x\ne\pm3\)
\(\dfrac{x+2}{3+x}-\dfrac{x}{3-x}=\dfrac{8x-6}{9-x^2}\\ \Leftrightarrow\dfrac{\left(x+2\right)\left(3-x\right)}{\left(3+x\right)\left(3-x\right)}-\dfrac{x\left(3+x\right)}{\left(3+x\right)\left(3-x\right)}-\dfrac{8x-6}{\left(3+x\right)\left(3-x\right)}=0\\ \Leftrightarrow\dfrac{-x^2+x+6-3x-x^2-8x+6}{\left(3+x\right)\left(3-x\right)}=0\\ \Leftrightarrow-2x^2-10x+12=0\\ \Leftrightarrow x^2+5x-6=0\\ \Leftrightarrow\left(x-1\right)\left(x+6\right)=0\\ \Leftrightarrow\left[{}\begin{matrix}x=1\left(tm\right)\\x=-6\left(tm\right)\end{matrix}\right.\)
\(a,\dfrac{3x+2}{6}-\dfrac{3x-2}{4}=\dfrac{15}{8}\)
\(\Leftrightarrow4\left(3x+2\right)-6\left(3x-2\right)=45\)
\(\Leftrightarrow12x+8-18x+12=45\)
\(\Leftrightarrow12x-18x=45-12-8\)
\(\Leftrightarrow-6x=25\)
\(\Leftrightarrow x=\dfrac{-25}{6}\)
Vậy \(S=\left\{\dfrac{-25}{6}\right\}\)
\(b,\dfrac{x+2}{3+x}-\dfrac{x}{3-x}=\dfrac{8x-6}{9-x^2}\left(ĐKXĐ:x\ne3;x\ne-3\right)\)
\(\Leftrightarrow\left(x+2\right)\left(3-x\right)-x\left(3+x\right)=8x-6\)
\(\Leftrightarrow3x-x^2+6-2x-3x-x^2=8x-6\)
\(\Leftrightarrow-x^2-x^2+3x-2x-3x-8x=-6+6\)
\(\Leftrightarrow-2x^2-10x=0\)
\(\Leftrightarrow-2x\left(x-5\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}-2x=0\\x-5=0\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=0\left(nhận\right)\\x=5\left(nhận\right)\end{matrix}\right.\)
Vậy \(S=\left\{0;5\right\}\)
\(\left|2x-3\right|-4x-9=0\)
<=> \(\left|2x-3\right|=4x+9\)
<=> \(\orbr{\begin{cases}2x-3=4x+9\left(x\ge\frac{3}{2}\right)\\3-2x=4x+9\left(x< \frac{3}{2}\right)\end{cases}}\) <=> \(\orbr{\begin{cases}2x=-12\\6x=-6\end{cases}}\) <=> \(\orbr{\begin{cases}x=-6\left(ktm\right)\\x=-1\left(tm\right)\end{cases}}\)
\(\left(x+1\right)^2-\left|5-3x\right|-x=x\left(x+2\right)+4\)
<=> \(\left|5-3x\right|=x^2+2x+1-x-x^2-2x-4\)
<=> \(\left|5-3x\right|=-x-3\)
<=> \(\orbr{\begin{cases}5-3x=-x-3\left(x\le\frac{5}{3}\right)\\5-3x=x+3\left(x>\frac{5}{3}\right)\end{cases}}\) <=> \(\orbr{\begin{cases}2x=8\\4x=2\end{cases}}\) <=> \(\orbr{\begin{cases}x=4\left(ktm\right)\\x=\frac{1}{2}\left(ktm\right)\end{cases}}\)
=> pt vô nghiệm
\(x^2-x-2x+2+4.\left(3x^2+9x+2x+6\right)=38\)
\(\Leftrightarrow x^2-3x+1+12x^2+44x+24=38\)
\(\Leftrightarrow13x^2+41x-13=0\)
\(\Leftrightarrow x^2+\frac{41}{13}x-1=0\)
\(\Leftrightarrow x^2+2.\frac{41}{26}x+\left(\frac{41}{26}\right)^2-1-\left(\frac{41}{26}\right)^2=0\)
\(\Leftrightarrow\left(x+\frac{41}{26}\right)^2=\frac{2357}{676}\)
\(\Leftrightarrow\orbr{\begin{cases}x+\frac{41}{26}=\frac{\sqrt{2357}}{26}\\x+\frac{41}{26}=-\frac{\sqrt{2357}}{26}\end{cases}}\Leftrightarrow\orbr{\begin{cases}x=\frac{\sqrt{2357}}{26}-\frac{41}{26}\\x=-\frac{\sqrt{2357}}{26}-\frac{41}{26}\end{cases}}\)
\(\Leftrightarrow\orbr{\begin{cases}x=\frac{\sqrt{2357}-41}{26}\\x=\frac{-\sqrt{2357}-41}{26}\end{cases}}\)